PENINGKATAN EFEKTIVITAS DAN HASIL BELAJAR PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN MELALUI PENERAPAN APLIKASI GOOGLE CLASSROOM SISWA KELAS VIII-C SMP NEGERI 6 MATARAM TAHUN PELAJARAN 2021/2022 - I GUSTI NYOMAN SAPTARI (GANEC SWARA, 2022)
The purpose of this study was to determine: the application of the Google Classroom application in increasing the effectiveness of learning PJOK in class VIII-C students of SMP Negeri 6 Mataram in the 2021/2022 academic year.The study used a classroom action research design that included the components of planning, action, observation and reflection, by taking the subjects of class VIIIC students of SMP Negeri 6 Mataram as many as 35 people consisting of 24 boys and 11 girls. The data were analyzed with Learning Management, learning effectiveness and student learning outcomes.The results show that: the application of the Google Classroom application can increase the effectiveness of learning PJOK in class VIII-C students of SMP Negeri 6 Mataram in the 2021/2022 academic year